UPAYA PENANGANAN TERJADINYA TINDAK PIDANA DI BANDARA INTERNASIONAL MINANGKABAU OLEH KEPOLISIAN SEKTOR KAWASAN BANDARA INTERNASIONAL MINANGKABAU - Ade Saputra; Iyah Faniyah (UNES Law Review, 2021)
Efforts to deal with the occurrence of crimes at Minangkabau International Airport by the Minangkabau International Airport Regional Police is to carry out investigations and investigations. Criminal acts that occur are still general crimes so that the handling is still carried out by the Police as is the handling of criminal acts in general. In the event of a special crime in the Minangkabau International Airport area, special handling will also be carried out. Criminal acts that specifically occur in airport areas such as aviation crime, narcotics crime, customs crime, smuggling and so on. Collaboration with various related institutions is carried out against these special crimes in terms of their handling. Obstacles in the Effort to Handling Criminal Actions at Minangkabau International Airport By the Regional Police of the Minangkabau International Airport Area is to socialize what the community should do in order to avoid criminal acts. Another obstacle is the lack of responsiveness of law enforcement officers to reports provided by victims, so that the process of handling crimes that occur at airports is slow. There are still many visitors who do not understand the environmental safety standards of the Minangkabau international airport.